Designing Evidence-Based Medicine Training to Optimize the Transfer of Skills From the Classroom to Clinical Practice: Applying the Four Component Instructional Design Model. (November 2015) - Maggio, Lauren A.; Cate, Olle ten; Irby, David M.; O'Brien, Bridget C.
Abstract : Evidence-based medicine (EBM) skills, although taught in medical schools around the world, are not optimally practiced in clinical environments because of multiple barriers, including learners' difficulty transferring EBM skills learned in the classroom to clinical practice. This lack of skill transfer may be partially due to the design of EBM training. To facilitate the transfer of EBM skills from the classroom to clinical practice, the authors explore one instructional approach, called the Four Component Instructional Design (4C/ID) model, to guide the design of EBM training. On the basis of current cognitive psychology, including cognitive load theory, the premise of the 4C/ID model is that complex skills training, such as EBM training, should include four components: learning tasks, supportive information, procedural information, and part-task practice. The combination of these four components can inform the creation of complex skills training that is designed to avoid overloading learners' cognitive abilities; to facilitate the integration of the knowledge, skills, and attitudes needed to execute a complex task; and to increase the transfer of knowledge to new situations. The authors begin by introducing the 4C/ID model and describing the benefits of its four components to guide the design of EBM training. They include illustrative examples of educational practices that are consistent with each component and that can be applied to teaching EBM. They conclude by suggesting that medical educators consider adopting the 4C/ID model to design, modify, and/or implement EBM training in classroom and clinical settings.